Influence of Added Synthetic Lysine for First Phase Second Cycle Commercial Leghorns with the Methionine+Cysteine/Lysine Ratio Maintained at 0.75 - Liu, Z.; Wu, G.; Bryant, M.M.; Sr., D.A. Roland (International Journal of Poultry Science, 2004)
A 3 x 4 factorial experiment with three protein levels (17.52, 16.24 and 15.22%) and four added synthetic lysine levels (0.0000, 0.0295, 0.0590 and 0.0884%) was conducted to determine the influence of adding synthetic lysine in er diets while maintaining a 0.75 Met+Cys/Lys ratio. In this experiment, a total of 1,440 Hy-Line W-36 hens (first phase of second cycle) were randomly divided into 480 cages with 3 birds per cage. Five adjoining cages consisted of a group and then the ninety-six groups were randomly assigned to 12 dietary treatments. The results showed there were no interactions (P > 0.05) between protein level and added synthetic lysine on feed intake, egg production, egg mass, egg weight or feed conversion. Protein effects were observed for feed intake (P < 0.01), egg production (P < 0.01), egg mass (P < 0.01), egg weight (P < 0.05) and feed conversion (P < 0.05). There was no difference (P > 0.05) obtained among the four supplemental synthetic lysine levels, indicating the influences of adding synthetic lysine on performances was not significant (P > 0.05) for hens fed diets containing a low protein level up to 15.22% and with feed intake at approximate 100 g/hen/day.